REFRAMING ISLAMIC EDUCATIONAL CONCEPT FOR SOCIAL JUSTICE - Affan Ramli (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
The development of concepts and theories of Islamic Education have started since the First Conference on Muslim Education in Mecca in 1997. However, throughout these concepts, the Muslims scholars fail to link the concept of Islamic Education with the struggle for social justice in the Muslim community. This paper aims to discuss why social justice issues seem to be overlooked, this paper also offers recommendation on reframing of Islamic educational theory. For this purpose, this paper analyzes documents resulted from the World Conferences of the Muslim Education, and from another conference with the theme Toward Construction of a Contemporary Islamic Educational Theory conducted in Amman-Jordan. The author found that Islamic education theories surprisingly devoid of social justice issues, and put more emphasis on individual development, simplification of the concept of society as mere group of individuals, and to avoid resistance (risks if taking confrontative issues such as social justice) from the dictatorial regimes holding power in Muslim countries